2014
DOI: 10.1097/ta.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Early propranolol administration to severely injured patients can improve bone marrow dysfunction

Abstract: BACKGROUND Bone marrow (BM) dysfunction is common in severely injured trauma patients, resulting from elevated catecholamines and plasma granulocyte colony-stimulating factor (G-CSF) as well as prolonged mobilization of hematopoietic progenitor cells (HPCs). We have previously shown that propranolol (β-blocker [BB]) reduces HPC mobilization in a rodent model of injury and hemorrhagic shock. We hypothesize that BB would prevent BM dysfunction in humans following severe injury. METHODS Forty-five severely inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 29 publications
(52 reference statements)
3
78
0
Order By: Relevance
“…The effect of propranolol in reducing capsular inflammation and thickness, and in modulating collagen deposition on textured implants observed in this experiment is consistent with findings from previous studies of others fibrosis conditions 19 , which showed that the application of nonselective beta-adrenoceptors antagonists inhibits maturation of collagen, reduces the number of vessels, collagen density, number of mast cells, eosinophils and myofibroblasts compared with control 22,23,25 .…”
Section: Effect Of Propranolol On Capsular Reaction Around Silicone Isupporting
confidence: 81%
See 3 more Smart Citations
“…The effect of propranolol in reducing capsular inflammation and thickness, and in modulating collagen deposition on textured implants observed in this experiment is consistent with findings from previous studies of others fibrosis conditions 19 , which showed that the application of nonselective beta-adrenoceptors antagonists inhibits maturation of collagen, reduces the number of vessels, collagen density, number of mast cells, eosinophils and myofibroblasts compared with control 22,23,25 .…”
Section: Effect Of Propranolol On Capsular Reaction Around Silicone Isupporting
confidence: 81%
“…Besides alteration of cellular activity related to inflammation, catecholamines stimulate vasoconstriction that causes hypoxia at the wound area and the increase of endothelial cell proliferation, vascular endothelial growth factor (VEGF) expression and angiogenesis. Also, catecholamines promote inhibition of eosinophil influx [23][24] .…”
Section: Effect Of Propranolol On Capsular Reaction Around Silicone Imentioning
confidence: 99%
See 2 more Smart Citations
“…We used a relatively low dose of propranolol in this study. Higher doses of propranolol may be indicated, as a recent study established that trauma patients could receive doses up to 2-mg IV early after admission depending on the HR [25]. Future studies should evaluate optimal propranolol dosing, and an American Association for the Surgery of Trauma multi-institutional study is forthcoming.…”
Section: Discussionmentioning
confidence: 93%